Association between Neutrophilic Granulocyte Percentage and Diabetes Mellitus in Cushing’s Syndrome Patients: A Cross-Sectional Study - Baomin Wang; Yumei Yang; Haoyue Yuan; Xiaomu Li (International Journal of Endocrinology)
Background. Glucose metabolism is frequently impaired in patients with Cushing’s syndrome (CS) due to chronic exposure to excess glucocorticoids. Inflammation plays an essential role in the pathophysiology of diabetes mellitus (DM). The present study aimed to investigate the potential associations of inflammatory blood cell parameters, including white blood cell (WBC) count, neutrophil count, neutrophilic granulocyte percentage (NEUT%), lymphocyte count (LYM), and lymphocyte proportion (LYM%), with diabetes mellitus in Cushing's syndrome patients. Materials and Methods. The cross-sectional study was conducted in Zhongshan Hospital of Fudan University, China. A total of 150 patients with Cushing’s syndrome were retrospectively screened from 2017 to 2019. The demographic data, clinical data, and blood samples (lipids, adrenal, glucose, and inflammatory blood cell parameters) were recorded. Statistical analyses were carried out by using the SPSS software package, version 13.0. Results. In this study, the prevalence of diabetes mellitus was 38.7% in patients with Cushing’s syndrome. Patients with DM had higher WBC, neutrophil, NEUT% levels than patients without DM (p<0.05). As the NEUT% increased, a stepwise increase in glucose and glycated hemoglobin (HbA1c) level was observed. In addition, in the multivariate logistic regression, NEUT% was a significant independent risk factor for DM, regardless of gender, age, body mass index (BMI), and triglyceride and 12 midnight cortisol (12 MN cortisol) level (OR = 2.542, 95% CI 1.337–4.835, p<0.001). Conclusions. In conclusion, elevated NEUT% level was linked to diabetes in patients with Cushing’s syndrome. The neutrophilic granulocyte percentage may be referred to as a new predictor for diabetes in Cushing’s syndrome patients.